Urinary Calprotectin and Posttransplant Renal Allograft Injury - Tepel, Martin (PLoS One, 2014)
OBJECTIVE: Current methods do not predict the acute renal allograft injury immediately after kidney transplantation. We evaluated the diagnostic performance of urinary calprotectin for predicting immediate posttransplant allograft injury. METHODS: In a multicenter, prospective-cohort study of 144 incipient renal transplant recipients, we postoperatively measured urinary calprotectin using an enzyme-linked immunosorbent assay and estimated glomerular filtration rate (eGFR) after 4 weeks, 6 months, and 12 months. RESULTS: We observed a significant inverse association of urinary calprotectin concentrations and eGFR 4 weeks after transplantation (Spearman r = −0.33; P<0.001). Compared to the lowest quartile, patients in the highest quartile of urinary calprotectin had an increased risk for an eGFR less than 30 mL/min/1.73 m(2) four weeks after transplantation (relative risk, 4.3; P<0.001; sensitivity, 0.92; 95% CI, 0.77 to 0.98; specificity, 0.48; 95% CI, 0.31 to 0.66). Higher urinary calprotectin concentrations predicted impaired kidney function 4 weeks after transplantation, as well as 6 months and 12 months after transplantation. When data were analyzed using the urinary calprotectin/creatinine-ratio similar results were obtained. Urinary calprotectin was superior to current use of absolute change of plasma creatinine to predict allograft function 12 months after transplantation. Urinary calprotectin predicted an increased risk both in transplants from living and deceased donors. Multivariate linear regression showed that higher urinary calprotectin concentrations and older donor age predicted lower eGFR four weeks, 6 months, and 12 months after transplantation. CONCLUSIONS: Urinary calprotectin is an early, noninvasive predictor of immediate renal allograft injury after kidney transplantation.